Content knowledge development in a chemistry teacher preparation program: A current potentials and challenges - Widhiyanti, T.; Treagust, D.; Mocerino, Mauro; Vishnumolakala, V. (2017)
© 2017 Author(s). One of the essential facets in teacher education program is the development of the teachers' content knowledge and it has been suggested by many scholars that the study to analyse the process of content knowledge development in teacher education program is necessary. Regarding this, the aim of this research is to evaluate the existing program of developing pre-service chemistry teachers' content knowledge, especially in the topic about the particulate nature of matter. The curriculum of content knowledge development was analysed using the forms of the curriculum evaluation (Akker, 1998; Goodlad, Klein, and Tye (1979); Treagust, 1987). Within this framework, the curriculum was evaluated in several aspects including the vision and intention of the curriculum as mentioned in the curriculum documents (intended curriculum), the users' interpretation and perception about the curriculum (perceived curriculum), the actual process of curriculum implementation (implemented curriculum), and the outcomes of the curriculum (achieved curriculum). According to the framework used for this study, the research combined qualitative and quantitative methods of data collection and the interpretation including document analysis, classroom observation, interviews, and two-tier diagnostic test. Through this research we examined the coherence among those aspects. The results reveal that although the content knowledge development is explicitly intended in a curriculum, its implementation and lecturers' perceptions give influence in the results as appear in pre-service teachers' achievements. In general, this research provides basic information about the effectiveness of the program including the challenges and the potentials for a reconsideration of the program in the future.